Premature birth as a risk factor for autism spectrum disorder. (3rd May 2016) - Goldin, Rachel L.; Matson, Johnny L.
Abstract: Objective : Autism spectrum disorder (ASD) is common, life-long in nature, and can be very debilitating. Thus, an intensive search is on to identify the potential risk factors for the disorder. Premature birth has been identified as one potential factor that could influence potential symptoms of ASD. Me thod : The sample for this study consisted of 1655 at risk children for developmental delays who were 17–37 months of age. Participants were divided into those diagnosed with ASD ( n  = 916) and children with atypical development only ( n  = 739). Re sults : Premature births were almost twice as common for the atypical development group versus the ASD group. Co nclusions : Implications of these data are discussed.